Complications of Hepatic Chemoembolization - Clark, Timothy W.I. (Thieme Medical Publishers, 2006)
Transarterial hepatic chemoembolization continues to evolve as an integral therapy for unresectable primary and secondary liver tumors. Despite relatively low morbidity, major complications may be seen. This article provides an overview of the spectrum of vascular and nonvascular complications related to this therapy.